A sparse deep learning approach for automatic segmentation of human vasculature in multispectral optoacoustic tomography - Chlis, Nikolaos-Kosmas; Karlas, Angelos; Fasoula, Nikolina-Alexia; Kallmayer, Michael; Eckstein, Hans-Henning; Theis, Fabian J.; Ntziachristos, Vasilis; Marr, Carsten (Photoacoustics, 2020)
Multispectral Optoacoustic Tomography (MSOT) resolves oxy- (HbO2) and deoxy-hemoglobin (Hb) to perform vascular imaging. MSOT suffers from gradual signal attenuation with depth due to light-tissue interactions: an effect that hinders the precise manual segmentation of vessels. Furthermore, vascular assessment requires functional tests, which last several minutes and result in recording thousands of images. Here, we introduce a deep learning approach with a sparse-UNET (S-UNET) for automatic vascular segmentation in MSOT images to avoid the rigorous and time-consuming manual segmentation. We evaluated the S-UNET on a test-set of 33 images, achieving a median DICE score of 0.88. Apart from high segmentation performance, our method based its decision on two wavelengths with physical meaning for the task-at-hand: 850 nm (peak absorption of oxy-hemoglobin) and 810 nm (isosbestic point of oxy-and deoxy-hemoglobin). Thus, our approach achieves precise data-driven vascular segmentation for automated vascular assessment and may boost MSOT further towards its clinical translation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Artificial intelligence; Clinical; Deep learning; Machine learning; Multispectral optoacoustic tomography; Segmentation; Translational